2003
DOI: 10.2337/diacare.26.3.837
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glucagon-Like Peptide 1 (7-36 Amide) on Insulin-Mediated Glucose Uptake in Patients With Type 1 Diabetes

Abstract: OBJECTIVE -To examine the insulinomimetic insulin-independent effects of glucagon-like peptide (GLP)-1 on glucose uptake in type 1 diabetic patients. RESEARCH DESIGN AND METHODS -We used the hyperinsulinemic-euglycemic clamp (480 pmol ⅐ mϪ2 ⅐ min Ϫ1 ) in paired randomized studies of six women and five men with type 1 diabetes. In the course of one of the paired studies, the subjects also received GLP-1 at a dose of 1.5 pmol ⅐ kg Ϫ1 ⅐ min Ϫ1 . The patients were 41 Ϯ 3 years old with a BMI of 25 Ϯ 1 kg/m 2 . The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…Moreover GLP-1 had no effect on pyruvate-induced glucagon secretion in isolated ␣-cells, in agreement with the earlier study where cAMP levels in ␣-cells were unaffected by GLP-1 (20). These findings correlate with studies in type 1 diabetic subjects where GLP-1 had no effect on plasma glucagon levels during a hyperinsulinemic-euglycemic clamp (21). Assertions that GLP-1 acts as a direct inhibitor of glucagon secretion are founded upon studies where paracrine factors may have mediated an apparent suppression.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover GLP-1 had no effect on pyruvate-induced glucagon secretion in isolated ␣-cells, in agreement with the earlier study where cAMP levels in ␣-cells were unaffected by GLP-1 (20). These findings correlate with studies in type 1 diabetic subjects where GLP-1 had no effect on plasma glucagon levels during a hyperinsulinemic-euglycemic clamp (21). Assertions that GLP-1 acts as a direct inhibitor of glucagon secretion are founded upon studies where paracrine factors may have mediated an apparent suppression.…”
Section: Discussionsupporting
confidence: 92%
“…We have also addressed the issue of a direct action of the gluco-incretin glucagon-like peptide 1 (GLP-1) on ␣-cell glucagon secretion. Despite assertions that GLP-1 directly modulates glucagon secretion (18,19), evidence to the contrary exists (20,21). To this end, we have studied ␣-cell activity at the level of the perfused pancreas, intact and dispersed islets, and fluorescence-activated cell sorter (FACS)-isolated adherent ␣-cells.…”
mentioning
confidence: 99%
“…To our knowledge, we are the first group of investigators who have shown a reduction in insulin clearance rate with prolonged administration of GLP-1. We have also observed this effect in an acute GLP-1 infusion protocol (240 min) in type 1 diabetic volunteers (11) We could not demonstrate change in the molar ratio of C-peptide to insulin during the hyperglycemic clamp in the GLP-1 treatment group. This is most likely due to the small changes in insulin secretion compared with changes in insulin levels during its exogenous administration and a possible type 2 error because of the small number of subjects.…”
mentioning
confidence: 62%
“…Recombinant GLP-1 (7-36 amide) was produced by prokaryotic fermentation, and a COOH-terminal amide was added to the peptide as previously described (11). This preparation is Ͼ99% pure and displays a single peak on highperformance liquid chromatography.…”
Section: Selection Of Volunteersmentioning
confidence: 99%
“…These data indicated a detachment between the dyslipidemia and hyperglycemia typically associated with insulin resistance. However, differences in non-insulin-mediated glucose uptake (17,18) may contribute to the discrepancy between insulin metabolic studies and plasma insulin and glucose assays.…”
Section: Discussionmentioning
confidence: 99%